Assessing the Impact of De-radicalisation and Counter-radicalism Initiatives: A Case Study of PW Fatayat NU in West and East Java, Indonesia - Neng Hannah; Risma Hikmawati; Ida Rochmawati; Dedih Wahyudin; Hirni Kifa Hazefa (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2025)
This study comprehensively evaluates de-radicalisation and counter-radicalism programs administered by the provincial branches of PW Fatayat NU in West Java and East Java, Indonesia. Employing a qualitative field research methodology, the study integrates data from document analysis, participant observation, semi-structured interviews with key organisational leaders and partners, and focus group discussions with diverse stakeholders. The analysis is framed by Kinsley’s seven organisational effectiveness dimensions—structure, strategy, systems, skills, style, staff, and shared values—offering a multidimensional perspective on program implementation and outcomes. Results reveal that while both provincial branches have established foundational organisational structures and strategic orientations conducive to program delivery, significant differences exist in system utilisation, professional capacity, and advocacy effectiveness. The West Java branch is characterised by strong interdepartmental coordination, effective communication channels, and well-defined governance structures. In contrast, the East Java branch faces challenges with strategic impact and resource mobilisation. Both branches demonstrate active stakeholder engagement through knowledge sharing, social reintegration, and policy advocacy. The study identifies critical constraints, including limited professional expertise, inconsistent communication practices, and insufficient collaborative networks, which impede optimal program performance. This research contributes to the growing scholarship on countering violent extremism (CVE) by foregrounding the importance of professional organizational management and inclusive multistakeholder engagement. It further underscores the imperative of gender-sensitive approaches and continuous capacity development to enhance program sustainability. These findings offer actionable insights for policymakers, civil society organisations, and government agencies committed to strengthening the efficacy and resilience of counter-radicalism interventions in complex socio-political environments.